Social and pedagogical factors influencing the formation of Lithuanian children literature at the end of the 19th century - Auryla, V. (Psichologija, 1963)
The article analyses the social and pedagogical factors which conditioned the formation of Lithuanian children literature at the end of 19th century. Most attention is paid to the fight of progressive people of that time for the democratization of education, education of the growing generation, preparation of Soviet-content reading books for children, preparation of realistic books for children in conditions of prohibition of Lithuanian writing.According to the documents, it is revealed how catholic clergy spoke against Soviet-content books for children, cursed and burned some of the publications. V. Kudirka, J. Šliūpas, S. Matulaitis, J. Jablonskis, and P. Mašiotas fought against clericalism in children literature. In their battle they resorted to the ideas of Russian pedagogues V. Vodovozov and K. Ušinsky who maintained the idea that children must be taught in their mother tongues. These educators revealed the anti-pedagogical character of the scholastic education and showed the damage of religious didactic reading to children and thus laid foundations to the appearance of realistic children literature and its criticism.The article discusses the literary works for children published in readers of that time and also written by J. Malinauskaitė-Eglė, J. Šliūpas, A. Kriščiukaitis-Aišbė.A separate unit discusses the articles by P. Mašiotas about the theory of Lithuanian children literature and also the reviews by J. Jablonskis, S. Matulaitis, and J. Tumas-Vaižgantas on individual creative works of children literature and books for children.The article concludes that catholic clergy, defending own and the governing class’ interests, was leading a ferocious battle against budding realist Lithuanian soviet-content children literature. This battle inferred much damage to Lithuanian children literature not only due to the Czarist prohibition of Lithuanian print, but also due to the fact that clergy adversely reacted to the progressive Lithuanian literature not containing religious content.
Keywords: children literature and history of pedagogy.